Implantable cardioverter-defibrillator therapy in hypertrophic cardiomyopathy: A SIMPLE substudy - Vamos, Mate; Healey, Jeff S; Wang, Jia; Connolly, Stuart J; Mabo, Philippe; Van Erven, Lieselot; Kautzner, Josef; Glikson, Michael; Neuzner, Jorg; O'Hara, Gilles; Vinolas, Xavier; Gadler, Frederik; et al. (Heart rhythm, 2018)
BACKGROUND: Patients with hypertrophic cardiomyopathy (HCM) are considered to be at high risk for elevated defibrillation thresholds, periprocedural complications, and failed appropriate shocks. OBJECTIVE: The purpose of this study was to determine the value of defibrillation testing (DT) in HCM patients undergoing implantable cardioverter-defibrillator (ICD) insertion. METHODS: Defibrillation thresholds, perioperative complications, and long-term outcomes were compared between patients with HCM and those with ischemic cardiomyopathy (ICM) or dilated cardiomyopathy (DCM) enrolled in the SIMPLE (Shockless IMPLant Evaluation) trial (Clinialtrials.gov Identifier: NCT00800384). In patients with HCM, outcomes were also compared between those randomized to DT vs no DT. RESULTS: Adequate defibrillation safety margin without system change was achieved in 46 of 52 (88.5%) HCM and 948 of 1047 (90.5%) ICM/DCM patients (P = .63). Perioperative complications occurred in 1 of 52 (1.9%) HCM patients with DT compared to 67 of 1047 (6.4%) ICM/DCM patients with DT (P = .37) or 3 of 42 (7.1%) HCM patients without DT (P = .32). During follow-up, there was no significant difference between HCM vs ICM/DCM patients in terms of all-cause mortality (adjusted hazard ratio [HR] 1.02, 95% confidence interval [CI] 0.45-2.34), composite of arrhythmic death or failed appropriate shock (adjusted HR 0.33, 95% CI 0.04-2.42), inappropriate shocks (adjusted HR 1.64, 95% CI 0.69-3.89), or system complications (adjusted HR 1.93, 95% CI 0.88-4.27). All-cause mortality (HR 0.26, 95% CI 0.03-2.20), appropriate (HR 0.24, 95% CI 0.03-2.05), and inappropriate shocks (HR 2.13, 95% CI 0.51-8.94) were similar in HCM patients without or those with DT. CONCLUSION: We did not find any difference in intraoperative defibrillation efficacy, perioperative complications, and long-term outcomes between patients with HCM and those with ICM/DCM. DT did not improve intraoperative or clinical shock efficacy in HCM patients.
Keywords: Hypertrophic cardiomyopathy; náhlá srdeční smrt; jednoduchá slepá metoda; Female; Implantable cardioverter–defibrillator; výsledek terapie; Death, Sudden, Cardiac; ženské pohlaví; Global Health; celosvětové zdraví; lidé; hypertrofická kardiomyopatie; Treatment Outcome; míra přežití; Electrocardiography; Cardiomyopathy, Hypertrophic; elektrokardiografie; prognóza; Single-Blind Method; Defibrillation testing; Incidence; Male; incidence; Prognosis; Survival Rate; Defibrillators, Implantable; lidé středního věku; mužské pohlaví; defibrilátory implantabilní; Middle Aged; Humans